In-plane structural performance of dry-joint stone masonry Walls: A spatial and non-spatial stochastic discontinuum analysis. (1st September 2021) - Pulatsu, Bora; Gonen, Semih; Erdogmus, Ece; Lourenço, Paulo B.; Lemos, Jose V.; Prakash, Ravi
Highlights: A stochastic discontinuum analysis is proposed considering material uncertainties. Effect of vertical stress on DJ-SMWs is investigated. Influence of interfacial resistance on DJ-SMWs is highlighted. Influence of spatial and non-spatial distribution of contact properties is explored. Ultimate performance limits and safety levels of the DJ-SMWs are identified. Abstract: In this study, the in-plane structural behavior, capacity, and performance of dry-joint stone masonry walls (DJ-SMWs) and the effects of the vertical stress level on these factors are investigated via a stochastic discontinuum analysis that considers the material uncertainty. A discontinuum type of analysis is performed based on the discrete element method (DEM), where each stone masonry unit is explicitly represented in the computational model. To better simulate the cracking and shear failure modes within the stone units, a coupled fracture energy-based contact constitutive model is implemented into a commercial discrete element code, 3DEC. First, the proposed modeling approach is validated by comparing to experimental findings in literature. Then, the approach is used to explore the failure mechanism and the force–displacement behavior of DJ-SMWs, considering different vertical stress levels and material properties. The results of the novel modeling strategy provide a better understanding of the progressive collapse mechanism of DJ-SMWs and the influence of the vertical stress level. Furthermore, the outcomes of this research indicate the major role of the frictional resistance at the joints in the safety and performance assessment of the dry-joint load-bearing masonry walls. Finally, important inferences are made regarding the non-spatial and spatial stochastic discontinuum analysis.